2002
DOI: 10.1103/physrevlett.88.095701
|View full text |Cite
|
Sign up to set email alerts
|

From Strong to Fragile Glass Formers: Secondary Relaxation in Polyalcohols

Abstract: We have studied details of the molecular origin of slow secondary relaxation near T(g) in a series of neat polyalcohols by means of dielectric spectroscopy and (2)H NMR. From glycerol to threitol, xylitol, and sorbitol the appearance of the secondary relaxation changes gradually from a wing-type scenario to a pronounced beta peak. It is found that in sorbitol the dynamics of the whole molecule contributes equally to the beta process, while in glycerol the hydrogen bond forming OH groups remain rather rigid com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(98 citation statements)
references
References 37 publications
7
90
1
Order By: Relevance
“…By varying the chain length n ¼ 1, 2, 3 and E7 and in a polymer (nE69), they found in dielectric spectra for nr3 b-relaxations manifest as excess wings, whereas a broad hump for nE7, and a distinct peak for the polymer (nE69). A similar result was observed in polyalcohols by Dö et al 47 These findings suggest that shortening the chain structures could suppress b-relaxations (other possible reasons are also noted in Ngai et al 48 ). In Pd-Ni-Cu-P MG systems, several studies from the electronic and atomic structural perspectives have uncovered that with the increasing of Cu contents, the MGs acquire deeper binding energy and develop more covalent-like bonding, and especially chain-like Pd-P-Pd/Cu atomic configuration was suggested [49][50][51] .…”
Section: Discussionsupporting
confidence: 75%
“…By varying the chain length n ¼ 1, 2, 3 and E7 and in a polymer (nE69), they found in dielectric spectra for nr3 b-relaxations manifest as excess wings, whereas a broad hump for nE7, and a distinct peak for the polymer (nE69). A similar result was observed in polyalcohols by Dö et al 47 These findings suggest that shortening the chain structures could suppress b-relaxations (other possible reasons are also noted in Ngai et al 48 ). In Pd-Ni-Cu-P MG systems, several studies from the electronic and atomic structural perspectives have uncovered that with the increasing of Cu contents, the MGs acquire deeper binding energy and develop more covalent-like bonding, and especially chain-like Pd-P-Pd/Cu atomic configuration was suggested [49][50][51] .…”
Section: Discussionsupporting
confidence: 75%
“…4. As reported in previous works [7][8][9], all three parameters for sugar alcohols show a strong dependence on both N C and N OH (filled symbols). However, since N C = N OH for sugar alcohols, the figures are identical and it is impossible to separate the effects of the two parameters.…”
Section: Resultsmentioning
confidence: 48%
“…1). It has been reported that sugar alcohols exhibit systematic increases in fragility and T g with increasing chain length [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the emergence of secondary relaxations, especially of the so-called Johari-Goldstein (JG) β-relaxation, has attracted the attention of the large scientific glass community. [4][5][6][7][8][9][10][11][12][13] This JG process is associated with local, noncooperative motions of the molecular unit as a whole, thus different from secondary relaxations -due to intramolecular degrees of freedom (e.g., side-chain motions in polymers) and indeed it was found even in single rigid molecules. 4,12 Despite the large quantity of available experimental and simulations studies, the nature of the local JG relaxation is still far from being understood.…”
Section: Introductionmentioning
confidence: 99%